Pemberantasan Tindak Pidana Money Laundering yang Berasal dari Tindak Pidana Narkotika - Juna Karo-Karo; Bismar Nasution; Madiasa Ablisar; Muhammad Ekaputra (USU LAW JOURNAL, 2019)
Abstract. One of the original crimes in the crime of money laundering is property acquired from narcotics crimes. Property acquired from the crime of narcotics transactions by both individuals and corporations is not directly used because of fear or indications of money laundering activities. For this reason, the perpetrators always try to hide the origin of these assets in various ways which include trying to include them in the financial system, ways taken in the form of hiding or disguising the origin of the assets with the intention of avoiding tracking efforts by the authorities. law enforcement as money laundering. The problems raised in this study, namely how the form of criminal law policy in overcoming the crime of money laundering originating from criminal acts of narcotics, the mechanism of criminal law enforcement against money laundering crimes originating from criminal acts of narcotics, and obstacles in the enforcement of criminal law against money laundering crimes originating from narcotics crime. In accordance with the above problems as for the purpose of this study is to find out and analyze the form of criminal law policy in dealing with criminal acts of money laundering originating from narcotics crime, the mechanism of criminal law enforcement against money laundering crimes originating from narcotics crimes, and obstacles barriers to criminal law enforcement against money laundering crimes originating from narcotics crimes. To find answers to these problems, this study uses a type of normative legal research that is descriptive analytical, where normative legal research uses secondary data as the main data by using data collection techniques carried out by means of library research (library reseacrh), and data analysis using methods qualitative data analysis.  Keywords: law enforcement, money laundering, narcotics crime.